Long-Term Dissemination of CTX-M-5-Producing Hypermutable Salmonella enterica Serovar Typhimurium Sequence Type 328 Strains in Russia, Belarus, and Kazakhstan - Kozyreva, Varvara K. (American Society for Microbiology, 2014)
In this paper, we present evidence of long-term circulation of cefotaxime-resistant clonally related Salmonella enterica serovar Typhimurium strains over a broad geographic area. The genetic relatedness of 88 isolates collected from multiple outbreaks and sporadic cases of nosocomial salmonellosis in various parts of Russia, Belarus, and Kazakhstan from 1996 to 2009 was established by multilocus tandem-repeat analysis (MLVA) and multilocus sequence typing (MLST). The isolates belong to sequence type 328 (ST328) and produce CTX-M-5 β-lactamase, whose gene is carried by highly related non-self-conjugative but mobilizable plasmids. Resistance to nalidixic acid and low-level resistance to ciprofloxacin is present in 37 (42%) of the isolates and in all cases is determined by various single point mutations in the gyrA gene quinolone resistance-determining region (QRDR). Isolates of the described clonal group exhibit a hypermutable phenotype that probably facilitates independent acquisition of quinolone resistance mutations.